HISTORY OF BANYUWANGI KALIKLATAK PLANTATION AND ITS IMPACT ON SURROUNDING COMMUNITIES - Mahfud, Mahfud; Yudiana, I Kadek; Sariyanto, Sariyanto (RADJA PUBLIKA, 2023)
The purpose and object of this paper is a relationship between the existence of the Kaliklatak plantation, as a European plantation, and its impact on the people of Onderafdeeling Kaliklatak during the colonial period 1900-1942. The method used in this study is a historical method to reconstruct the history of plantations and their impact on community development in Onderafdeeling Kaliklatak. The data collection technique used refers to the first stage in the historical method, namely the heuristic process, searching for and collecting historical sources. Data analysis techniques relate to the second, third and fourth stages in the historical method which include source criticism, interpretation and historiography. Based on research results and conclusions, then the opening of coffee and rubber plantations during the colonial era in Onderafdeeling Kaliklatak is very much related to the natural condition of this area and also to changes in colonial politics, open the door. The first company to expand was NV Maatschappij owned by van E. Moormann&Co, producing the main crop of Robusta coffee which is in high demand worldwide. The relevance of opening large plantations to the people of Onderafdeeling Kaliklatak can be seen in several ways. First, there is a change in the position of local elites as landlords close to the colonial. Second, helping to create